2020
DOI: 10.1016/j.ekir.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, and Immunological Features of a Cluster of COVID-19–Contracted Hemodialysis Patients

Abstract: Background: The outbreak of highly contagious coronavirus disease 2019 (COVID-19) has posed a serious threat to human life and health, especially for those with underlying diseases. However, the impact of COVID-19 epidemic on hemodialysis (HD) centers and HD patients has not been reported. Methods: We reviewed the whole course of the COVID-19 in the HD center of Renmin Hospital, Wuhan University (from January 14, 2020, to March 12, 2020). We compared the clinical manifestation and immune profiles among differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 16 publications
(23 reference statements)
1
69
3
1
Order By: Relevance
“…42,43 In addition, a lower percentage of patients with pre-existing kidney disease (regardless of whether treated by dialysis) reported respiratory symptoms (shortness of breath and cough) and fever compared with patients without kidney disease. These findings are consistent with existing reports 23,37 and highlight the necessity of vigilance for nontraditional COVID-19 symptoms such as altered mental status and gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…42,43 In addition, a lower percentage of patients with pre-existing kidney disease (regardless of whether treated by dialysis) reported respiratory symptoms (shortness of breath and cough) and fever compared with patients without kidney disease. These findings are consistent with existing reports 23,37 and highlight the necessity of vigilance for nontraditional COVID-19 symptoms such as altered mental status and gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…[11][12][13] We also found that dialysis patients receiving ICU-level care for COVID-19 had an in-hospital death rate of 50%, which is lower than rates reported in regional studies. [36][37][38] Strikingly, the unadjusted death rate among nondialysis patients with CKD (51%) was equivalent to that of dialysis patients (50%) yet notably higher than that of patients without underlying kidney disease (35%). These findings not only highlight the importance of discussing COVID-19 risks with patients with CKD, regardless of whether they are receiving maintenance dialysis, but also engaging in advance care planning conversations in the ambulatory setting, before patients falling ill with COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…An immune-deficient state was indeed demonstrated by Ma et al in their study [8]. A significantly lower number of T cells, natural killer cells, and B cells in ESRD-HD patients was seen compared with patients not on dialysis [8].…”
Section: Discussionmentioning
confidence: 68%
“…This was also observed firsthand by the authors by being on the frontlines in New Rochelle, New York, one of the first COVID-19 epicenters in the United States. Only one other group of researchers has described a lower severity of disease in dialysis patients with COVID-19 [8]. In that study, Ma et al describe mostly mild clinical symptoms in patients with ESRD and a low likelihood of progression to severe pneumonia in ESRD-HD patients in an outpatient setting.…”
Section: Discussionmentioning
confidence: 98%
“…In Wuhan, China, 12% of the dialysis center staff at Renmin Hospital contracted COVID-19, whereas in Lombardy, Italy, a 33% infection rate was reported among the hospital dialysis staff. 2,3 To that end, we have 4 reports published in Kidney International Reports from Wuhan, China; the Lombardy region of northern Italy; London, England; and Paris, France 2-5 detailing their early experience with COVID-19 outbreaks affecting patients with end-stage renal disease at outpatient dialysis facilities and leading to a large number resulting in hospitalization and, often, death, similar to our experience in New York City. 6 Based on the aggressiveness of testing, these reports show an infection rate of 11% to 26% among patients with end-stage renal disease.…”
mentioning
confidence: 87%